Comparison of Salivary Biochemical Composition between End Stage Renal Disease and Healthy Subjects - Mahin Bakhshi; Soheila Manifar; Fahimeh Sadat Tabatabaei; Bita Joz-khaje noori; Siamak Sabour; Fatemeh Rezaei Dokht
Introduction: Following the renal disease involvement, some variations may occur in the flow, pH and biochemical components of the saliva; therefore, saliva possibly would be a useful tool for diagnosis and monitoring of the renal disease through evaluation of the components. The aim of the present study was to analyse the biochemical composition of the saliva in patients undergone haemodialysis for the end-stage renal disease (ESRD) in Imam Khomeini Hospital. Materials & Methods: In this descriptive cross-sectional study, 64 haemodialysis patients and 67 healthy individuals were selected and their salivary samples were obtained by spitting method. Salivary biochemical factors were determined by serum kits and auto-analyzer while the samples' pH was determined by an automatic pH meter. Then, Creatinine, Ca, Mg, urea, α-amylase parameters as well as the salivary flow rate were measured. The saliva biochemical compositions were analyzed using Student t test. Results: The mean (± standard deviation) of the salivary flow rate was statistically lower in ESRD patients than healthy ones (0.34±0.22 ml/min vs. 0.57±0.29 ml/min: P<0.001). Salivary pH (7.87±0.72 vs. 6.99±0.4: P<0.001) and concentrations of urea (134.4±40.8 vs. 40.8±15.1 mg/dl: P<0.001); Cr (1.1±0.9 vs. 0.4±0.1 mg/dl: P<0.001) and α-amylase (1107.4±788.4 vs. 568.3±437.0 mg/dl: P<0.001) were statistically higher in ESRD patients than healthy controls. Ca was significantly lower in ESRD patients than healthy ones (2.8±2.8 vs. 3.6±2.0 mg/dl: P<0.05).). No significant differences were noted between both groups regarding salivary Mg. The mean (± standard deviation) age was statistically higher in ESRD patients than healthy ones (63.2±15.4 years vs. 48.2±15.3 years: P<0.001). No significant differences were noted between both groups regarding weight and gender. Conclusion: Due to the significant alternations of the salivary biochemical concentrations in ESRD patients; saliva can be used as a diagnostic tool for monitoning the involvement of the renal diseases.